Pengaruh Gender-Role Identity dan Gender-Role Attitudes terhadap stres akademik pada sistem pembelajaran dalam jaringan (daring) mahasiswa di Kabupaten Banggai - Siti Khadijah Kitta; Muhammad Tamar; Mansyur Radjab (Yinyang: Jurnal Studi Islam Gender dan Anak, 2022)
This study aims to look the effect of gender-role identity and gender-role attitudes on academic stress on the online learning system of students at universities in Banggai Regency. Respondents of this study amounted to 326 respondents. The sampling technique used is simple random sampling. The data collected were analyzed using multiple linear regression to see the effect of the independent variables gender-role identity and gender-role attitudes on the dependent variable academic stress. The results of the study found that gender-role identity, the feminine category, had a significant effect on academic stress with a positive relationship direction, while gender-role attitudes had a significant effect on the direction of a negative relationship direction with academic stress. This means that the higher the feminine quality possessed by the individual, the higher the level of academic stress he has. As for attitudes toward gender roles, the more transcendent an individual's gender role attitude is, the lower the level of academic stress will be. On the other hand, the sexism of the gender role attitude of the individual, the higher the level of academic stres. The contribution of gender-role identity and gender-role attitudes simultaneously to academic stress is 6.9%.